Hsp90 mutants with distinct defects provide novel insights into cochaperone regulation of the folding cycle. - Rebecca Mercier; Danielle Yama; Paul LaPointe; Jill L Johnson (PLoS Genetics)
Molecular chaperones play a key role in maintaining proteostasis and cellular health. The abundant, essential, cytosolic Hsp90 (Heat shock protein, 90 kDa) facilitates the folding and activation of hundreds of newly synthesized or misfolded client proteins in an ATP-dependent folding pathway. In a simplified model, Hsp70 first helps load client onto Hsp90, ATP binding results in conformational changes in Hsp90 that result in the closed complex, and then less defined events result in nucleotide hydrolysis, client release and return to the open state. Cochaperones bind and assist Hsp90 during this process. We previously identified a series of yeast Hsp90 mutants that appear to disrupt either the 'loading', 'closing' or 'reopening' events, and showed that the mutants had differing effects on activity of some clients. Here we used those mutants to dissect Hsp90 and cochaperone interactions. Overexpression or deletion of HCH1 had dramatically opposing effects on the growth of cells expressing different mutants, with a phenotypic shift coinciding with formation of the closed conformation. Hch1 appears to destabilize Hsp90-nucleotide interaction, hindering formation of the closed conformation, whereas Cpr6 counters the effects of Hch1 by stabilizing the closed conformation. Hch1 and the homologous Aha1 share some functions, but the role of Hch1 in inhibiting progression through the early stages of the folding cycle is unique. Sensitivity to the Hsp90 inhibitor NVP-AUY922 also correlates with the conformational cycle, with mutants defective in the loading phase being most sensitive and those defective in the reopening phase being most resistant to the drug. Overall, our results indicate that the timing of transition into and out of the closed conformation is tightly regulated by cochaperones. Further analysis will help elucidate additional steps required for progression through the Hsp90 folding cycle and may lead to new strategies for modulating Hsp90 function.